Brazil on screen : cinema novo, new cinema, utopia - Nagib, Lucia (Tauris world cinema series., 2007)
What connects films of a particular nation, in a particular time? What makes them especially interesting and revealing? This book offers an original answer to these central questions for world cinema, focusing on the case of Brazil and the return of the utopian gesture into its cinema. In this extensively illustrated book, Lúcia Nagib argues that the foundational utopian imaginary that has permeated culture in Brazil since the time of the first discoverers has had a decisive influence on its film aesthetics, especially at creative peaks, such as the Cinema Novo movement of the 1960s and early '70s, and the cinematic revival from the mid 1990s onwards. She shows how utopian motifs like images of the sea or the classical Greek myth of Orpheus establish a bridge between these two periods, guaranteeing thereby historical continuity from a cinema concerned with the national project to another engaged in a globalised dialogue. In focus are classics of Cinema Novo, such as 'Black God, White Devil', 'Land in Anguish' and 'How Tasty was my Little Frenchman', alongside representatives of a more recent transnational aesthetics, including the anti-utopian 'City of God'and the urban dystopia of 'The Trespasser'.